Morbidity Burden in Patients With Ebstein Anomaly: The Natural History - Filip Eckerström; Vibeke Elisabeth Hjortdal; Peter Eriksson; Mikael Dellborg; Zacharias Mandalenakis (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The lifetime morbidity burden of patients with Ebstein anomaly (EA) has not been well described. Methods and Results Through an extensive 2‐country register‐based collaboration, patients diagnosed with EA who were born between 1930 and 2017 were identified in Danish and Swedish nationwide medical registries. Each patient was matched by age and sex with 10 control subjects from the general population. Cox proportional‐hazards regression, Fine–Gray competing risk regression, and Kaplan–Meier failure function were used to estimate the morbidity burden. The study included 794 patients diagnosed with EA and 7940 controls, with a median follow‐up period of 33 years. Among patients with EA, approximately half (n=442) had isolated EA, and 28% (n=218) had concomitant atrial septal defect. Patients with complex anatomy demonstrated the highest cardiovascular morbidity burden, followed by those with concomitant atrial septal defect and isolated EA. The lifetime cumulative incidence of supraventricular arrhythmia and ventricular preexcitation in patients with EA, with or without atrial septal defect, was approximately 70% and 19%, respectively. Supraventricular arrhythmia substantially increased the risk of ischemic stroke (hazard ratio [HR] 22.6 [95% CI, 11.1–45.9]). Presence of atrial septal defect significantly affected arrhythmia and heart failure burden compared with isolated EA. In the total cohort of patients with EA, supraventricular arrhythmia onset led to an immediate high incidence of heart failure, with a 10‐year cumulative incidence of 18%. Conclusions The natural history of EA, whether isolated or not, involves a substantial burden of cardiovascular morbidity and thus a highly vulnerable long‐term prognosis.